Accessing Finance for Innovative EU SMEs Key Drivers and Challenges - Laura Vasilescu (Economic Review: Journal of Economics and Business, 2014)
Small and medium enterprises (SMEs) play a vital role in economic development, they offer the most economical use of capital in relation to job creation and provide the strongest channel for development and innovation. Innovation is recognized as an essential component of the economic growth process, broadly defined as development, deployment and economic utilization of new products, processes and services. SMEs are crucial for helping economies to restructure quickly in response to changing economic, social and market conditions, under the impact of international financial crisis. However, SMEs can fulfill this potential if they obtain the finance necessary to start and develop their businesses. Access to finance is a key determinant for business start-up, development and growth for SMEs, including the innovative ones, and they have different needs and face different challenges. The limited market power, lack of management skills, absence of adequate accounting records and insufficient assets, transaction costs and lack of collateral, all tend to increase the risk profile of SMEs. Moreover, uncertainty and informational asymmetries that characterize SMEs are amplified for innovative SMEs making it more difficult for them to access finance through traditional means. The current economic environment has brought SME needs into particular focus given the significantly tightened credit supply conditions arising from the reduced ability and willingness of banks to provide financing. In order to improve the access to finance for SMEs, the efforts should be focused at the European and national levels on solving the problems regarding working capital, improving entrepreneurship and financial environment in the long term, attracting new financial resources, facilitating dialogue and consultation between governments, SMEs and financial institutions.
Keywords: G32; M13; O31; 330; financing; innovative SMEs; financial crisis